Natural history and extracutaneous involvement of congenital morphea: Multicenter retrospective cohort study and literature review. Issue 6 (6th September 2018) - Mansour, Mark; Liy Wong, Carmen; Zulian, Francesco; Li, Suzanne; Morishita, Kimberly; Yeh, Eluen Ann; Stewart, Katie; Laxer, Ronald M.; Pope, Elena
Abstract: Background: Congenital morphea is a form of localized scleroderma that presents at birth. There is limited information on its presentation and progression. Methods: Patients with congenital morphea were identified from five pediatric dermatology and rheumatology tertiary care centers in Canada, the United States, and Italy from 2001 to 2016. Cases from the literature were identified by searching Ovid (EMBASE and MEDLINE) from inception to June 30, 2017. Disease characteristics and prevalence of extracutaneous involvement were analyzed. Results: Thirteen patients were identified from the five centers, and 13 cases were described in the literature, representing 25 patients, with one duplication. Fourteen patients (56%) were female. Median age at diagnosis was 2.9 years (interquartile range 1.2‐5.1 years). Linear morphea, including en coup de sabre and Parry‐Romberg syndrome, was the most common subtype observed (n = 19, 76%), followed by circumscribed (n = 5, 20%), generalized (n = 2, 8%), and mixed (n = 2, 8%). The face (n = 14, 56%), scalp (n = 8, 32%), and trunk (n = 6, 24%) were the most common locations affected. Most lesions were active at diagnosis (n = 19, 76%), but all patients with follow‐up later became inactive. Extracutaneous involvement was seen in 12 (48%) patients, all of whom had linear morphea. Musculoskeletal sequelae were seen in those with linear morphea of the extremities (4/5, 80%), and neurologic involvement was seen in those with linear morphea of the head (8/13, 62%). Conclusion: Congenital morphea is associated with extracutaneous manifestations and delayed diagnosis. More research is needed to determine whether early recognition, monitoring, and treatment can alter the disease course.